Video. - Kunz, Martin; London, Barbara; Weibel, Peter; Musée d'Art et d'Histoire, Genève; Stampa, Basel (Genève : Association Musée d'Art Moderne, 1977)
Otth, Jean ; Glass, Philip ; Chaimowicz, Marc Camille ; Chiari, Giuseppe ; Lucier, Alvien ; Weibel, Peter ; etc.
Video, Musée d'Art et d'Histoire, Genève et par STAMPA, Bâle, Avril - Mai 1977
Frans & Engels
kunstcatalogus